COLLEGE ADMINISTRATION SYSTEM - Jayasudha S.; Rubina L.; Gayathri A.; Judithacquline S. (Galaxy International Interdisciplinary Research Journal, 2022)
The Project entitled “COLLEGE ADMINISTRATION SYSTEM”. The College admission process usually done manually by the college which takes a long time to complete the admission process. It takes long time to complete the admission of a single student .To overcome this , we planned to go for online admission. For analizing the datas, It helps to list all datas in excel format. Students need to register their details. Like, Name, Email, Phone, and address. They fill their +2 marks. All the given informations will be stored and analised by Admin. Students and Admin will get email confirmation after new registration.Admin needs to approve or disapprove based on given details. Approved students can be able to login to their panel. In students dashboard, they can view their suggested courses. List of courses and eligibility. Using If else comment in programming, All the inputs will be analised and chart will be prepared. Shotlisted students can pay their admission fees through online. For paid members, courses will be allotted in order. All the processes are done by programmingSo, error free admission is possible in all the ways. Its is designed by WORDPRESS as Frontend and MYSQL as Backend.